2019
DOI: 10.3389/fpsyt.2019.00176
|View full text |Cite
|
Sign up to set email alerts
|

NOP Receptor Agonist Ro 64-6198 Decreases Escalation of Cocaine Self-Administration in Rats Genetically Selected for Alcohol Preference

Abstract: Cocaine dependence is a psychiatric condition for which effective medications are still lacking. Published data indicate that an increase in nociceptin/orphanin FQ (N/OFQ) transmission by NOP receptor activation attenuates cocaine-induced place conditioning and the locomotor sensitization effects of cocaine. This suggests that the activation of the N/OFQ receptor (NOP) may attenuate the motivation for psychostimulants. To further explore this possibility, we investigated the effect of the potent and selective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Data on alcohol self-administration were recently paralleled in cocaine. We demonstrated that the NOP agonist Ro64-6198 reduced escalated cocaine self-administration in msP but not in Wistar rats [ 195 ], while Cippitelli and colleagues demonstrated that another NOP agonist, AT-312, decreased escalated cocaine self-administration and cocaine hedonic set point in Sprague Dawley rats [ 196 ].…”
Section: Role Of N/ofq-nop Receptor System In the Interaction Between Stress And Drug Addictionmentioning
confidence: 99%
“…Data on alcohol self-administration were recently paralleled in cocaine. We demonstrated that the NOP agonist Ro64-6198 reduced escalated cocaine self-administration in msP but not in Wistar rats [ 195 ], while Cippitelli and colleagues demonstrated that another NOP agonist, AT-312, decreased escalated cocaine self-administration and cocaine hedonic set point in Sprague Dawley rats [ 196 ].…”
Section: Role Of N/ofq-nop Receptor System In the Interaction Between Stress And Drug Addictionmentioning
confidence: 99%
“…These data suggest that the efficacy of AT‐312 in altering cocaine self‐administration is a function of NOP affinity and potency of AT‐312, compared with that of AT‐202, rather than a function of its selectivity. This hypothesis is supported by a recent study in a rat line with upregulated NOP receptor expression, where NOP receptor activation attenuates cocaine self‐administration 42 . To rule out a possible contribution by mu activation in eliciting the observed reduction of cocaine taking, and confirm that it is due to activation of NOP receptors, AT‐312 was administered following treatment with the NOP receptor antagonist SB‐612111.…”
Section: Discussionmentioning
confidence: 65%
“…The drug addiction mechanisms are complex and include desire, withdrawal, and relapse. Further studies are needed to verify how NOP agonists can attenuate drug addiction and induce depression (Li et al, 2019).…”
Section: Discussionmentioning
confidence: 99%